1997
DOI: 10.1152/jn.1997.77.2.797
|View full text |Cite
|
Sign up to set email alerts
|

Human Lumbosacral Spinal Cord Interprets Loading During Stepping

Abstract: Studies suggest that the human lumbosacral spinal cord can generate steplike oscillating electromyographic (EMG) patterns, but it remains unclear to what degree these efferent patterns depend on the phasic peripheral sensory information associated with bilateral limb movements and loading. We examined the role of sensory information related to lower-extremity weight bearing in modulating the efferent motor patterns of spinal-cord-injured (SCI) subjects during manually assisted stepping on a treadmill. Four non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
364
3
16

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 551 publications
(406 citation statements)
references
References 39 publications
23
364
3
16
Order By: Relevance
“…Thus, supraspinal input may not be required for integrating load information. For example, weight-bearing load has been shown to modulate lower limb muscle activity in individuals with spinal cord injury (Harkema et al, 1997). This supports the notion that afferent input regarding weight-bearing load is integrated within the spinal cord.…”
Section: Modulation Of Ankle Muscle Postural Reflex Magnitude Followisupporting
confidence: 67%
See 2 more Smart Citations
“…Thus, supraspinal input may not be required for integrating load information. For example, weight-bearing load has been shown to modulate lower limb muscle activity in individuals with spinal cord injury (Harkema et al, 1997). This supports the notion that afferent input regarding weight-bearing load is integrated within the spinal cord.…”
Section: Modulation Of Ankle Muscle Postural Reflex Magnitude Followisupporting
confidence: 67%
“…Harkema et al (1997) found that EMG amplitude during treadmill induced stepping in individuals with spinal cord injury was less coupled to muscle length (i.e. muscle spindle input) factors than to peak limb load.…”
Section: Modulation Of Ankle Muscle Postural Reflex Magnitude Followimentioning
confidence: 92%
See 1 more Smart Citation
“…One of these features, limb loading during stance, has recently been shown to dramatically enhance motor output from muscles of this limb in persons with complete (and incomplete) spinal cord transections, supporting the idea that the isolated spinal cord correctly interpretes proprioceptive a erent information in the sense of maintaining upright body position. 9,14 Applying these rules, elements of stepping on the treadmill short of complete step cycles, could recently be evoked in a 13-year old girl completely paralysed below spinal segment Th 6 12 (detailed manuscript in preparation; see also Wernig and MuÈ ller 5 and Wernig et al 6 for further reports on elements of stepping after complete spinal cord transection, and Dobkin et al 16 and Dietz et al 17 for phasic and alternating¯exor and extensor muscle activity during aided stepping).…”
Section: Discussionmentioning
confidence: 99%
“…Instead of focusing on the corticospinal tract and trying to train the phylogenetically youngest part of the motor system first, it may be beneficial to adopt an approach where we try to influence the motor system at the lowest level initially, namely, by influencing the CPGs, the phylogenetically older system. From several group studies, 15,21,25 it was highlighted that circuitry in the human species is able to learn, especially when this training is combined with loadbearing. We should consider the fact that the corticospinal tract is not the only tract to project to the motoneurons in the spine.…”
Section: Discussionmentioning
confidence: 99%